Biodiesel vegetal con diesel PEMEX en un motor de bomba de mando mecánico. Emisiones y prestaciones - Cárdenas Campuzano, Adrián; Tinajero Cruz, Beatriz; Villanueva Zúñiga, Sergio (My University, 2013)
Biodiesel vegetal con diesel PEMEX en un motor de bomba de mando mecánico. Emisiones y prestaciones
Biodiesel vegetal con diesel PEMEX en un motor de bomba de mando mecánico. Emisiones y prestaciones
Keywords: Biodiesel vegetal con diesel PEMEX en un motor de bomba de mando mecánico. Emisiones y prestaciones